2001
DOI: 10.1177/1524838001002001001
|View full text |Cite
|
Sign up to set email alerts
|

Why Battered Women Do Not Leave, Part 2

Abstract: This article is Part 2 of a review of factors hindering battered women's chances of leaving violent relationships. Part 1 covered major external inhibiting factors (e.g., women's economic dependency and the shortcomings of the criminal justice system). Part 2 centers on additional external inhibiting factors, such as inadequate social support from workplaces and community agencies, and addresses internal inhibiting factors, including the processes and effects of socialization, psychological and victimization e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(56 citation statements)
references
References 305 publications
2
43
1
2
Order By: Relevance
“…For instance, based on the 1985 National Family Violence Survey, only about seven percent of wife assaults are reported to the police (3% of minor abuse incidents and 14% of severe abuse incidents) (Kantor andStraus, 1990 andGelles, 1988). There are multiple reasons cited throughout the literature as to why the victims of domestic violence do not report it or do not leave the situation (e.g., Barnett, 2001 andEhrensaft andVivian, 1996). Most clients who receive counseling do not report domestic violence as a problem to their therapist.…”
Section: Challenges In the Assessment Of Domestic Violencementioning
confidence: 99%
“…For instance, based on the 1985 National Family Violence Survey, only about seven percent of wife assaults are reported to the police (3% of minor abuse incidents and 14% of severe abuse incidents) (Kantor andStraus, 1990 andGelles, 1988). There are multiple reasons cited throughout the literature as to why the victims of domestic violence do not report it or do not leave the situation (e.g., Barnett, 2001 andEhrensaft andVivian, 1996). Most clients who receive counseling do not report domestic violence as a problem to their therapist.…”
Section: Challenges In the Assessment Of Domestic Violencementioning
confidence: 99%
“…Aggressive behavior at home can happen in any personal or familial relationship, regardless of whether the gatherings are living respectively or not, whether they are hitched or cohabiting or living in three-generational more distant families. It is this social component, instead of area that characterizes the brutality as 'household' [4] Women's presentation to abusive behavior at home, in the midst of different variables, could be credited to their financial positions [5], especially in patriarchal society where they are generally impeded [6]. Financial variables interweaved with patriarchal society put the females in subordinate position, which thus have repercussions for three imperative spaces of females to be specific; the real space, Hira Abbas and Muhammad Waseem Shah: Relationship Between Perceived Stress, Life Satisfaction and Self Esteem Among Females Facing Domestic Violence the individual space and the subjective space.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Very few qualitative studies discussed the relationship dynamics between the abusive husband and wife. [15][16][17][18][19][20] Studies from developing countries demonstrated that the women experienced a conflict of emotions and developed coping mechanisms. They did not want to leave their abusing partners due to patriarchal society, financial dependency on husbands, fear and considering violence as normal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They did not want to leave their abusing partners due to patriarchal society, financial dependency on husbands, fear and considering violence as normal behaviour. [18][19][20][21] In India, data on coping mechanism within DV were unexplored. The objective of the study was to find out the trigger point of DV and coping strategies among women who had experienced DV by their affectionate husbands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation